Breakthroughs spotlighting roles for extracellular nucleotides and apyrases in stress responses and growth and development - Clark, Greg B (Plant science : an international journal of experimental plant biology, 2014)
Copyright © 2014 Elsevier Ireland Ltd. All rights reserved.